Prevalence and risk factors of Ascaris lumbricoides infection in children of Manusak Village, Kupang District, East Nusa Tenggara Province, Indonesia - Meliance Bria; Heny Arwati; Indah Setyawati Tantular (Universitas Muhammadiyah Surabaya, 2021)
ABSTRACT Worm infection is one of the health problems in all tropical countries, including Indonesia. The most frequent helminthiasis is the infection caused by the Soil-Transmitted Helminth. Primary school-age children are an age group that is susceptible to helminthiasis. Worm infections can cause a serious impact if left untreated with no clean and healthy lifestyle. This study was conducted to determine the prevalence and risk factors of STH in children of Manusak Village, East Kupang Subdistrict, Kupang District, East Nusa Tenggara Province, followed by the characterization of subjects. The analytic observational design with the cross-sectional study was applied to this research. Research subjects were 130 children aged 6-12 years old. The infection was diagnosed microscopically by the Katokatz method. Ascaris lumbricoides were the only species found infecting a total of 50 children (38.4%.). The distribution of ascariasis was higher in girls (30 or 23.08%) than in boys (20 or 15.38%), in children whose parents have no formal education (41 or 31.54%), and who their professions are a farmer. Poor hygiene and sanitation such as no washing hands with soap (27 or 20.77%) as well as the habit of not wearing footwear (47 or 36.2%) and bowel habit on the open areas (35 or 26.92%) are the risks factors causing the high incidence of A. lumbricoides in the studied area. Enlightenment to the parents regarding good personal and environmental hygiene and sanitation along with chemotherapy from the government and related agencies is needed to achieve a durable reduction of the burden of ascariasis and other STH infection. Keywords : Soil Transmitted Helminth, Ascaris lumbricoides, children, Kupang DistrictCorrespondence : heny-a@fk.unair.ac.id